Monitoring and evaluation of policy influence and advocacy - Tsui, Josephine; Hearn, Simon; Young, John (ODI, 2014)
Policy influence and advocacy are increasingly regarded as a means of creating sustainable policy change in international development. It is often also seen as a difficult area to monitor and evaluate. Yet ther e is an increasingly rich strand of innovation in options to monitor, evaluate and learn from both the successes and failures of policy infl uence and advocacy interventions. This paper explores current trends i n monitoring and evaluating policy influence and advocacy; discusses d ifferent theories of how policy influence happens; and presents a numb er of options to monitor and evaluate different aspects of advocacy in terventions. Case studies describe how some organisations have used th ese options in practice to understand their impact and improve their a dvocacy strategies.